Jacob Riis : reporter and reformer - Pascal, Janet B. (Oxford University Press, 2005)
Charts the course of Jacob Riis's work as a police reporter, which took him into the worst of New York's ghettos and tenements. Shows how his book, How the Other Half Lives, brought to life an entire reform movement. Characterizes his alliance with the young Theodore Roosevelt's battle to reform the New York police, breaking the brutal system of corruption and graft that had prevented the possibility of any real change in poor neighborhoods.